PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN: STUDI KASUS PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Farhatun Fauziah; Sari Karmiyati (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This research aims to determine the influence of employee value added capital (VACA), human capital value added (VAHU) and structured capital value added (STVA) on the financial performance of agricultural sector companies on the Indonesia Stock Exchange for the 2017-2021 period. The method used in this research is a quantitative approach. The data used is secondary data in the form of the company’s annual financial report. The data analysis techniques in this research are descriptive analysis, classical assumption testing, model feasibility testing, multiple regression analysis, hypothesis testing and model testing measured using SPSS. The partial analysis results show that value added capital employed (VACA) has a t value of -1.724 where -1.724 < 2.024 with a significance value of 0.093 > 0.05, which means that value added capital employed (VACA) has no significant effect on the company’s financial performance. Value added human capital (VAHU) has a calculated value of -1.415 where -1.415 < 2.024 with a significance value of 0.166 > 0.05, which means that value added human capital (VAHU) has no significant effect on the company’s financial performance. Meanwhile, the structure capital value added (STVA) t value is 2.165, where 2.165 > 2.024, which means that the structure capital value added (STVA) has a positive and significant effect on the company’s financial performance. The results of the simultaneous analysis obtained a value of Fcount (2.118) < Ftable (2.852) with a significant level of 0.115 > 0.05, meaning that value added capital employed (VACA), value added human capital (VAHU) and structure capital value added (STVA) simultaneously did not influence the company’s financial performance. The coefficient of determination (R2) is 0.150 or 15%, which means that value added capital employed (VACA), value added human capital (VAHU) and structure capital value added (STVA) contribute 15% to the company’s financial performance, while the remainder is 85% can be explained by other variables outside the research